Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1989)
Number of pages: 16

A Report to Superior Council of Education on the State and Needs of Education in 1985 from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1985)
Quebec Federation of Home and School Associations (QFHSA), founded in 1944 is an independent voluntary parental organization representing approximately six thousand families, mainly within the English speaking communities throughout the province. Parent volunteers are active within local Home and School associations, the national level through the Canadian Home and School Parent Teacher Federation. One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to reform and the advancement of the education of the child. thus we are pleased to submit this report on the state and needs of education as requested by the Superior Council of Education.

A Statement from Quebec Federation of Home and School Associations to the Superior Council of Education on the State of the Condition of Teaching in the Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1984)
Quebec Federation of Home and School Associations (QFHSA) is a parent group, working as volunteers at the school, provincial and national levels. QFHSA takes particular pride in the fact, that over the last forty years, parents, as volunteers, have seconded the schools' efforts to provide assistance in areas of school life, to upgrade or enhance the school's environment and, thereby, benefit the students. As an adjunct to direct involvement at the school level, though its resolutions addressed, over the years, to various levels involved in the educational process, QFHSA has pinpointed areas its members felt needed either more funding, changing, support, introduction, etc., as the case may be. These will be referred to specifically later on.